G519 Integrated child health at scale: the inreach story – lessons learnt from the development of joint paediatric clinics in primary care. (25th October 2020) - Macaulay, CP; Lemer, C; Lamb, S; Wolfe, I
Abstract : Aims: Over the last 3 years we have been developing and testing new models of integrated care for children and young people (CYP) in South London. As part of this we have developed a model of 'Inreach clinics' held in GP practices, jointly between GPs and Paediatricians. The overall aim is to improve care and outcomes for children. We report on our learning and successes of this journey. Methods: GP Practices were grouped into 'clusters' according to geography and population, each 'cluster' hosting one Inreach clinic per month. Initial challenges were commitment of GP time to host clinics, and shared patient notes and clinic management. Over time Paediatricians gained access to GP IT systems and notes were recorded locally. Lunch time 'lunch and learn' sessions for neighbouring practices after clinics were poorly attended so we developed the concept of a Patch Paediatrician (PP), giving GPs easy access for advice and referrals. We have honed referral pathways and introduced primary care prescribing by the PP. Clinics are currently jointly funded by the hospital and CCGs. Results: Currently 10 general paediatric consultants run monthly Inreach clinics in 16 patches, across 54 practices. We are conducting both service and research evaluations. Early results show reduction of ED attendances by 7 % and NEL admissions by 6 % . Patient satisfaction data shows that the vast majority of patients feel that the care received was good or very good. GPs report enhanced knowledge, clinical practice and confidence in managing children's health. Conclusions: Over the last 2 years we have completed several PDSA cycles responding to challenges and feedback. We have demonstrated several successes of this model of care. Our current model aligns clinics and the role of 'patch paediatrician' to the newly created Primary Care Networks, for strong GP ownership. We are further aligning these clinics with our targeted population approach to biopsychosocial care for CYP with ongoing conditions. We are now evaluating, at scale, the best possible evidence-based model of care.